Learning to Create Anecdotal Texts Using the Project Base Learning (Pjbl) Learning Model in Class X Odd Semester Students of SMKN 1 Setu Bekasi Regency the Academic Year 2021/2022 - Enok Hasanah (International Journal Labs, 2022)
Background: Anecdotal text is used to convey criticism, but not in a crude and hurtful way. The project Base Learning (PjBL) learning model is a learning model that focuses on problem-solving Objective: This study aims to determine the learning process of making anecdotal texts using the Project Base Learning (PjBL) learning model for class X odd semester students at SMKN 1 Setu, Bekasi Regency for the 2021/2022 academic year. Method: The research method used is a descriptive method with a qualitative approach. Data collection techniques use observation and documentation techniques. Results: The results of the study show that the implementation of anecdotal writing learning in class X of SMKN 1 Setu in Bekasi Regency has been carried out according to the steps of the Project Based Learning (PJBL) learning model. Meanwhile, the relationship between the Project Based Learning (PJBL) learning model and anecdotal texts is interrelated. Conclusion: Based on the research conducted, it can be concluded that the implementation of anecdotal writing learning in class X of SMKN 1 Setu in Bekasi Regency has been carried out according to the steps of the Project Based Learning (PJBL) learning model.